PENGGUNAAN PATI SAGU DENGAN SUBTITUSI TEPUNG DAUN KELOR DALAM PEMBUATAN KERUPUK SAGU - Fadel Muhammad; Shanti Fitriani; Yanti Nopiani (SAGU, 2025)
Crackers are snacks made from starch-containing ingredients. The raw material for making crackers is basically tapioca. Efforts to diversify sago crackers need to be made to increase protein content, one of which is by adding moringa flour. This study aimed to determine the effect of the ratio of sago starch and moringa flour on the physicochemical and organoleptic properties of sago crackers. The treatment in this study was the ratio of sago starch and moringa flour namely: SK1 (100:0), SK2 (95:5), SK3 (90:10), and SK4 (85:15). The data obtained were statistically analysed using analysis of variance and continued with duncan’s multiple range test (DMRT) at a 5% level. The results of variance analysis showed that the ratio of sago starch and moringa flour used significantly affected moisture, ash, protein, and fat contents, expandability, breakability, descriptive and hedonic sensory assessment, and overall assessment of crackers. The best treatment in this study was the SK2 (95:5) with characteristics of moisture content of 3.36%, ash content of 0.02%, protein content of 2.86%, fat content of 12.71%, expandability of 38.89%, breakability of 2.75 N/s with descriptive sensory assessment of greenish beige color, moringa leaf aroma, moringa leaf flavor, crispy, and overall rating was liked by the panellists.